Polyurethane Degrading Bacteria Isolated from Decayed Teak Wood (Tectona grandis Linn. f.) - Farah Aldila; Ari Susilowati; Ratna Setyaningsih (UIN Sunan Gunung Djati Bandung, 2019)
Polyurethane is a class of polymers characterized by their substantial tensile strength and high melting points which enables them to be extremely durable. Despite its xenobiotic origin, polyure-thane has been found susceptible to biodegradation by microorgan-isms. The main object of this research was to investigate polyurethane degradation by the bacterium isolated from decayed teak wood (Tec-tona grandis Linn. f.). Polyurethane degrading bacteria were isolated using selective medium in the form of LB (Luria Bertani) with the ad-dition of 0.3% Impranil. Bacterial biodegradation activities shown by the changes of polyurethane structure analyzed by FT-IR spectrosco-py. The bacterial identification was carried out based on observations on the morphological characteristics of the colonies, cell morphology and sequences of 16S rRNA encoding genes. One of the potential iso-late that successfully isolated was K9, which demonstrates the disap-pearance of the 1735/cm peak of the characteristic function urethane in the FT-IR analysis. Analysis of the 16S rRNA encoding gene showed that the potential isolate having 98% similarity index to Bacillus safen-sis strain FO-36b. The activity shown by the isolate suggests that the bacteria could be a promising agent for polyurethane degradation.